Current Trends in Improving of Artificial Joints Design and Technologies for Their Arthroplasty - Poliakov, Aleksandr; Pakhaliuk, Vladimir; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2020)
According to some reports, joint diseases are observed in almost 25% of people aged 30 years, and serious diseases such as arthrosis and arthritis develop in 90% of people over 55 years of age. They are accompanied by degradation of cartilage, joint deformities and persistent pain, which leads to limited mobility and a significant deterioration in the quality of life of patients. For the treatment of these diseases in the late stages, depending on the indications, various methods are used, the most effective of which are methods of joint arthroplasty and, in particular, total arthroplasty. Currently, total arthroplasty is one of the most effective and high-quality surgical operations. However, complications may arise after it, leading, inter alia, to the need for repeated surgical intervention. In order to minimize the likelihood of complications, the artificial joints used in total arthroplasty and the technology of their implantation are constantly being improved, which leads to the emergence of new designs and methods for their integration with living tissues. In this work, based on an analysis of the current state of hardware and technology for joint arthroplasty, predictive evaluations of their improvement directions are made.